2019
DOI: 10.14712/23362936.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Gas7 in the Subgranular Zone of Mice Hippocampus

Abstract: It is established that neural stem cells (NSC) reside in the hippocampal subgranular zone (SGZ) and contribute to neurogenesis throughout life. Although the molecular events that regulate hippocampal neural stem cell differentiation are known, the precise mechanism is undefined. Here, the role of growth arrest specific 7 (Gas7) protein in SGZ neural progenitor cell differentiation was studied. Immunoblotting and immunohistochemistry for Gas7 were performed on 12 weeks old mice hippocampus. The results displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Studies have shown that it is involved in the growth of nerve axons in vitro. Increased expression of Gas7 can promote the mi- gration of neurons; inhibition of its expression can suppress the migration process of neurons [8][9][10]. It has been found that a high level of Gas7 expression protects neurons from damage caused by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it is involved in the growth of nerve axons in vitro. Increased expression of Gas7 can promote the mi- gration of neurons; inhibition of its expression can suppress the migration process of neurons [8][9][10]. It has been found that a high level of Gas7 expression protects neurons from damage caused by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the independent expression of Disc1 and Gas7 protein in rodent brain [8, 12, 13]. But to-date, no studies have shown their co-expression in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for immunohistochemistry was performed as per the protocol described in the previous publication [12]. In specific, mice were euthanized with sodium pentobarbital (100 mg/kg) and perfused with ice-cold phosphate-buffered saline (PBS), followed by 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that growth arrest-specific (GAS) proteins play an important role in the regulation of multiple biological processes such as microfilament organization, neuronal differentiation, apoptosis, tyrosine kinase receptor activity, and control of the cell cycle progression [257][258][259][260][261][262]. GAS7, located on chromosome 17p13.1 [106], is expressed in early embryonic cells, testis, and neurons of several regions of the brain [263][264][265][266]. Furthermore, it has been demonstrated that GAS7 is expressed in the optic nerve and lamina cribrosa, which belongs to the connective tissue network via which the nerve fibers traverse to create the optic nerve, and it is predicted that the mentioned structure may constitute the main site for glaucomatous damage to the optic nerve.…”
Section: Gas7mentioning
confidence: 99%